2020
DOI: 10.1016/j.jcis.2020.02.105
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation versus imbibition in a porous medium

Abstract: Predicting and controlling the liquid dynamics in a porous medium is of large importance in numerous technological and industrial situations. We derive here a general analytical solution for the dynamics of a flat liquid front in a porous medium, considering the combined effects of capillary imbibition, gravity and evaporation. We highlight that the dynamics of the liquid front in the porous medium is controlled by two dimensionless numbers: a gravity-capillary number G and an evaporation-capillary number E. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 65 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…The sweat channel width ( w c ) is another important parameter for sweat collection, as it determines the travel rate of the sweat. Although Darcy’s law, Lucas-Washburn equation [ 38 ], Modifications to Darcy’s law and LW equation [ 39 ], Richards equation [ 40 ], and flow simulation or visualization tools [ 41 ] can approximately calculate the micro-fluid flow behavior in paper material, fluid imbibition into paper is a complex process governed by a highly coupled system of length and time-scaled parameters. Therefore, the sweat channel width in filter paper is typically determined by experiment, traditionally called a trial-and-error strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The sweat channel width ( w c ) is another important parameter for sweat collection, as it determines the travel rate of the sweat. Although Darcy’s law, Lucas-Washburn equation [ 38 ], Modifications to Darcy’s law and LW equation [ 39 ], Richards equation [ 40 ], and flow simulation or visualization tools [ 41 ] can approximately calculate the micro-fluid flow behavior in paper material, fluid imbibition into paper is a complex process governed by a highly coupled system of length and time-scaled parameters. Therefore, the sweat channel width in filter paper is typically determined by experiment, traditionally called a trial-and-error strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Capillary transport has been considered by many authors, both without [52][53][54] and with [55][56][57] evaporation. Its effect is to redistribute a solute deposited on a dry substrate.…”
Section: Advection-dispersion Equationsmentioning
confidence: 99%
“…In the analytical models, different external effects are considered separately. Van Engeland et al 35 have shown the simultaneous effects of capillary, gravity, and evaporation on liquid imbibition through porous media. However, in all practical applications, capillary action, evaporation, swelling, barrier effects, and gravitational effects all work together to cause a liquid to rise through a porous medium.…”
Section: ■ Introductionmentioning
confidence: 99%